Cybertrooping and the online manipulation of political communication in Malaysia: The Barisan Nasional years - Cheong, Niki (2020)
This study examines the illiberal practice used by state and political actors in Malaysia—known as ‘cybertrooping’—to manipulate communication practices and information flow on the internet while Barisan Nasional—the political coalition that had ruled the country since independence in 1957 until May 2018—were in power. It contributes to existing scholarly work on ‘computational propaganda’, ‘astroturfing’ and ‘trolling’, including the many studies that emerged following the political developments globally since the United Kingdom EU referendum and the United States Presidential Elections in 2016. This thesis argues that cybertrooping can be understood as an extension of a political party or state’s illiberal attempt at orchestrating a covert operation aimed at gaining or retaining power beyond media control and the threat of legislation, often referred to as the ‘chilling effect’. It will argue that cybertrooping extends known methods historically associated with political communication, including propaganda, public relations, spin and psychological operations, aided by internet affordances.